I found a nice general formula for the Taylor series of $\tan x$:

$$\tan x = \sum_{n\,=\,1}^\infty \frac {(-1)^{n-1}2^{2n} (2^{2n}-1) B_{2n}} {(2n)!} x^{2n - 1} $$

where $B_n$ are the Bernoulli numbers and $|x| < \dfrac {\pi} 2$.

I've tried Googling for a proof but didn't find anything. Hints would be appreciated too.

I am using the typical definition of the Bernoulli numbers:

$$\frac x {e^x - 1} = \sum_{n\,=\,0}^\infty \frac {B_n x^n} {n!}$$


The only non zero $B_n$ with odd index is $B_1=-1/2$, So $$ \sum_{n=0}^\infty\frac{B_{2n}}{(2n)!}x^{2n}=x\left(\frac{1}{e^x-1}+\frac{1}{2}\right) =\frac{x}{2}\coth\left(\frac{x}{2}\right) $$ which is valid for $|x|<2\pi$. Applying this with $x=it$, we get for $|t|<2\pi$: $$ \sum_{n=0}^\infty\frac{(-1)^nB_{2n}}{(2n)!}t^{2n}= \frac{t}{2}\cot\left(\frac{t}{2}\right) $$ Now note that $$ \cot(t)-2\cot(2t)=\frac{1-\cos^2t }{\sin t\cos t}=\tan t $$ so, for $|t|<\dfrac{\pi}{2}$ we have $$\eqalign{ t\tan t&=t\cot(t)-2t\cot(2t)\cr &=\sum_{n=0}^\infty\frac{(-1)^nB_{2n}2^{2n}}{(2n)!}t^{2n} -\sum_{n=0}^\infty\frac{(-1)^nB_{2n}4^{2n}}{(2n)!}t^{2n}\cr &=\sum_{n=1}^\infty\frac{(-1)^nB_{2n}2^{2n}(1-2^{2n})}{(2n)!}t^{2n}\cr &=t\sum_{n=1}^\infty\frac{(-1)^{n-1}B_{2n}2^{2n}(2^{2n}-1)}{(2n)!}t^{2n-1} } $$ From this the desired expansion follows.$\qquad\square$.


$$\frac z{e^z-1}+\frac z 2=1+\sum_{n=2}^\infty\frac{B_n}{n!}z^n$$ Replace $z$ with $2iz$ to get $$\color{red}{z\cot(z)}=\frac{iz(e^{iz}+e^{-iz})}{e^{iz}-e^{-iz}}=1+\sum_{n=2}^\infty\frac{B_n}{n!}(2iz)^n=1+\sum_{n=1}^\infty\frac{B_{2n}}{(2n)!}(-1)^n(2z)^{2n}$$ Now use following trigonometric formula $$\tan(z)=\cot(z)-2\cot(2z).$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.